On the Inverse Laplace Transform - Hernández-Galeana, A. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this work, we demonstrate that the Tuan-Duc formula employed for inverting the Laplace transform is equivalent to the expression provided by Post-Widder.